Emerging (In)Determinacy. (8th February 2018) - Eva, Benjamin
Abstract : In recent years, a number of authors have defended the coherence and philosophical utility of the notion of metaphysical indeterminacy. Concurrently, the idea that reality can be stratified into more or less fundamental 'levels' has gained significant traction in the literature. Here, I examine the relationship between these two notions. Specifically, I consider the question of what metaphysical (in)determinacy at one level of reality tells us about the possibility of metaphysical (in)determinacy at other more or less fundamental levels. Towards this end, I propose a novel conception of the way in which fundamental states of affairs determine derivative states of affairs in the presence of indeterminacy and construct a corresponding formal model of multilevel systems that demonstrates the compatibility of determinacy at the fundamental level with indeterminacy at higher levels (and vice versa), thereby rebutting Barnes' (2014) suggestion that indeterminacy at any level of reality implies indeterminacy at the fundamental level.